Coastal Landscape and Public Use. A Landscape Architecture Proposal for the Los Limites Beach, Chubut, Argentina - Belén Bonaz, María (Ri-Vista. Research for landscape architecture, 2017)
Along the Argentinian Patagonia Coast private urbanization develops over public beach areas. This study presents the case of an area called Los Limites Beach situated along the Patagonian coast. After an analysis, survey and diagnosis of natural and social features, a landscape project was developed having the objective to protect Patagonian coastal landscape identity, preserving its natural components and encouraging its public use.